Fabrication of Iron oxide nanoparticle loaded recycled PET nanofibers for water purification applications - Amira Hassan; Ahmed Abd El-Aziz; Mohamed Elwi; Anke Klingner (Discover Materials)
Abstract This study investigates the development and performance of polyethylene terephthalate (PET) nanofibers, made from recycled PET bottles, for water purification applications. The research focuses on incorporating Iron Oxide (Fe3O4) nanoparticles into fibrous PET membranes, optimizing their performance for heavy metal ions removal. By refining the electrospinning process, the study successfully produced uniform nanofibers with enhanced filtration capabilities. A significant difference in the fibers’ properties was observed by varying polymer concentrations in the electrospinning solution. Nanofibers produced at a 10 wt% concentration exhibited the highest tensile strength of 66 MPa and a balanced flexibility, making them suitable for high-pressure filtration scenarios. The fibers at 15 wt% demonstrated remarkable ductility with an elongation at break of 162%, ideal for dynamic filtration systems. The introduction of Iron Oxide (Fe3O4) nanoparticles significantly increased the Ultimate Tensile Strength to 86 MPa. Adsorption tests revealed that the 10 wt% fibers had the highest capacity for copper ions removal at 12 mg/g, attributed to their smaller fiber diameter and larger surface area. The addition of Fe3O4 nanoparticles further improved the adsorption capacity, reaching 19.8 mg/g for heavy metal ions. This enhancement is attributed to the high surface energy and strong affinity of Fe3O4 for contaminants. These findings underscore the potential of PET nanocomposites in providing efficient and sustainable water purification solutions, with performance tailored by adjusting polymer concentrations and nanoparticles integrations.